Managing an international tourism destination [videorecording] - Garner, Simon; Video Education Australasia (Australia : Video Education Australasia, 2006)
This program examines the importance of tourism to local economies. It covers all aspects of managing an international tourist destination using The Great Ocean Road as a case study. The broad topics covered include a description of the region and why it is a tourist destination; who visits The Great Ocean Road; managing tourism at the international level; managing tourism at the local level; how tourism benefits the region and some of the challenges that are subsequently created.
Executive producer, Mark McAuliffe ; editor, Zane Lovitt ; senior producer, Richard Leigh
Voice over, Maureen Sherlock
DVD format
Keywords: Tourism -- Victoria -- Case studies; Great Ocean Road (Vic.)